Marine bioactive compound dieckol induces apoptosis and inhibits the growth of human pancreatic cancer cells PANC‐1. Issue 2 (14th October 2020) - Xu, Jian Wei; Yan, Ye; Wang, Lei; Wu, Dong; Ye, Nai Kuan; Chen, Shi Hong; Li, Feng
Abstract: Pancreatic cancer, which threatens the global population, is a very aggressive disease with an increased mortality rate. Regarding the types of cancer, pancreatic cancer is prone to display significant resistance to conventional therapy, therefore there 5‐year survival rate is only 2% to 9%. Bioactive metabolites of marine algae such as polysaccharides, chitin, carternoids, and sterols possess immense pharmacological properties and tend to be promising alternatives for cancer treatment. Dieckol is one such polyphenolic bioactive compound extracted from brown algae Ecklonia cava, which is proven to possess antioxidant, anti‐inflammatory, antibacterial, antidiabetic properties. Therefore in the present study, we analyzed the anticancer property of dieckol on PANC‐1 pancreatic carcinoma cells. The cytotoxicity property of dieckol against PANC‐1 cells was assessed with 3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyl tetrazolium bromide assay, and cell morphological analysis. The generation of reactive oxygen species by dieckol on PANC‐1 was analyzed with DCFH‐DA staining and confirmed by quantifying antioxidants levels in untreated and dieckol‐treated PANC‐1 cells. The induction of apoptosis was further evaluated with different staining techniques such as Rhodamine 123 staining, acridine orange/ethidium bromide staining, DAPI staining, propidium iodide staining and was confirmed by estimating the protein expression of apoptotic genes, Bax and Bcl2. Cell adhesion assay and estimation of inflammatory cytokines were performed to detect the inhibitory effect of dieckol against cancer cell progression. It is further confirmed by analyzing cancer cell progression proteins, that is, proliferating cell nuclear antigen and cyclin D1 expressions in untreated and dieckol‐treated PANC‐1 cells. Our overall results authentically prove dieckol persuasively induces apoptosis and inhibits the progression of human pancreatic cancer cells in vitro, suggesting dieckol as a potent marine‐based phytochemical to treat pancreatic cancer.